2022
DOI: 10.1007/s11356-022-18532-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of traffic noise pollution using geographic information system and descriptive statistical method: a case study in Mashhad, Iran

Abstract: Environmental consequences and the epidemiologic results of noise pollution have chronic effects leading to widespread complications in the long run. As far as we know, there are a few studies for pollution monitoring and control systems in comparison with other environmental pollutants. One of the largest metropolitan cities located in Iran is Mashhad city as known as one of the biggest religious cities in the world. Different properties of this city including historical, industrial, and religious draw thousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The questionnaires of this research are standard and are taken from the models approved by previous researchers. Research tool also has structural validity [14,18]. A five-point Likert scale was used to assess and extract the opinion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaires of this research are standard and are taken from the models approved by previous researchers. Research tool also has structural validity [14,18]. A five-point Likert scale was used to assess and extract the opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Reference Relevant questions Subsequent [18] 1~3 Altruism [19] 4~6 Conscience [20] 7~10 chivalry [21] 11~13 Civil behavior [22] 14~16 Politeness and consideration…”
Section: Table 2 Five Dimensions Of Organizational Citizenship Behavi...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently few documents in the field of road traffic speed prediction, so this article draws on the literature surrounding several other issues in traffic prediction. At present, many scholars have conducted research in the field of traffic prediction [21,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is an unwanted sound that constitutes nuisance to the environment [1] and ranks third as the most hazardous form of pollution behind air and water pollution" [2]. "The Environmental and epidemiological consequences of noise pollution are chronic and has widespread complications in the long run" [3]. "It has been suggested that 12% or more of the global population is at risk of hearing loss from noise, which equates to well over 600 million people" [4].…”
Section: Introductionmentioning
confidence: 99%